Amphiphilic Triazine-Phosphorus Metallodendrons Possessing Anti-Cancer Stem Cell Activity - Evgeny K. Apartsin; Nadezhda Knauer; Ulf Dietrich Kahlert; Anne-Marie Caminade (MDPI AG, 2022)
Dendritic molecules bearing metal complexes in their structure (metallodendrimers and metallodendrons) are considered prospective therapeutic entities. In particular, metallodendrons raise interest as antitumor agents for the treatment of poorly curable or drug-resistant tumors. Herein, we have synthesized amphiphilic triazine-phosphorus dendrons bearing multiple copper (II) or gold (III) complexes on the periphery and a branched hydrophobic fragment at the focal point. Due to their amphiphilic nature, metallodendrons formed single micelles (mean diameter ~9 nm) or multi-micellar aggregates (mean diameter ~60 nm) in a water solution. We have tested the antitumor activity of amphiphilic metallodendrons towards glioblastoma, a malignant brain tumor with a notoriously high level of therapy resistance, as a model disease. The metallodendrons exhibit higher cytotoxic activity towards glioblastoma stem cells (BTSC233, JHH520, NCH644, and SF188 cell lines) and U87 glioblastoma cells (IC50 was 3-6 µM for copper-containing dendron and 11-15 µM for gold-containing dendron) in comparison with temozolomide (IC50 >100 µM)-the clinical standard of care for glioblastoma. Our findings show the potential of metallodendron-based nanoformulations as antitumor entities.